2009
DOI: 10.2134/jeq2008.0379
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Removal Rates in Subsurface Media Estimated From Published Studies of Field Experiments and Large Intact Soil Cores

Abstract: Information about the microbial removal efficiencies of subsurface media is essential for assessing the risk of water contamination, estimating setback distances between disposal fields and receiving waters, and selecting suitable sites for wastewater reclamation. By analyzing published data from field experiments and large intact soil cores, an extensive database of microbial removal rates was established for a wide range of subsurface media. High microbial removal rates were found in volcanic soils, pumice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 151 publications
(225 reference statements)
4
106
4
Order By: Relevance
“…Most of the facilities using groundwater in these studies obtained water from aquifers located in karst regions. These, along with those located in limestone and crystalline (fractured bedrock) settings are likely to have higher virus concentrations than in other settings 8,15,16 . USEPA virus methods specify sampling volumes of 200 L (ICR) to 300 L (Method 1615) of surface water and 1,000 L (ICR) to 1,500 L (Method 1615) of groundwater 17,18 .…”
Section: Introductionmentioning
confidence: 95%
“…Most of the facilities using groundwater in these studies obtained water from aquifers located in karst regions. These, along with those located in limestone and crystalline (fractured bedrock) settings are likely to have higher virus concentrations than in other settings 8,15,16 . USEPA virus methods specify sampling volumes of 200 L (ICR) to 300 L (Method 1615) of surface water and 1,000 L (ICR) to 1,500 L (Method 1615) of groundwater 17,18 .…”
Section: Introductionmentioning
confidence: 95%
“…Hynds et al (2012) estimated that the approximate zone of impact of septic tanks extended up to 110 m up-gradient of the wellhead, if high 120-h prior precipitation rates were considered. Conversely, in a review, Pang (2009) reported that the maximum observed E. coli transport distance was as great as 920 m, for sewage polluted groundwater in gravel aquifers in Burnham, New Zealand, at velocities as high as 56-153 m/ day (Sinton 1980). Future studies might investigate the cut-off distance for spatial autocorrelation as related to microbial transport in different hydrogeological environments.…”
Section: Spatial Regressionmentioning
confidence: 99%
“…Many factors affect bacterial removal rates in soil under saturated conditions. These include physical-chemical properties of soil, properties of bacteria, solution chemistry, inactivation, physical straining, heterogeneity and preferential flow paths (Pang, 2009). …”
Section: Removal Of Bacteriamentioning
confidence: 99%